Comparison of Date Milk and Oxytocin Massage on Increasing Breast Milk Production in Breastfeeding Mothers in the Jiput Health Center Working Area, Pandeglang Regency, 2022 - Novi Anggiani; Lili Farlikhatun (Jurnal EduHealth, 2023)
Based on data obtained from the Jiput Health Center in Pandeglang Regency, in the last two years, the coverage of exclusive breastfeeding for infants has continued to decline and is very far from the target expected by the government, namely 80% of babies must receive exclusive breastfeeding. In 2020 the coverage of exclusive breastfeeding decreased to 78.65% and in 2021 it continued to decrease to 66.9%. This study aims to determine the comparison between giving date milk and oxytocin massage to increasing milk production in breastfeeding mothers in the Work Area of the Jiput Health Center, Pandeglang Regency in 2022. Methods: used a quasi-experimental method with a two group pretest and posttest design approach. This research design has two groups, namely the experimental group and the control group. The effectiveness of the treatment was assessed by comparing the posttest and pretest scores. Data analysis used the Wilcoxon and Mann Whitney tests. samples taken in this study were 36 respondents. The results showed that after being given date milk from 18 respondents, some respondents (66.7%) produced breast milk smoothly, while after giving oxytocin massage, most of the respondents (88.9%) produced milk smoothly. The results of the analysis with the Wilcoxon test showed that there was an effect of giving dates on increasing milk production (P_value 0.001) and the effect of oxytocin massage on increasing milk production (P_value 0.000). The conclusion of this study is that there is no difference in the effectiveness of giving dates with oxytocin massage on milk production. It can be concluded that both date milk and oxytocin massage have good benefits for increasing milk production.